Immunomodulatory Plants against Coronavirus: A Comprehensive Review with Emerging Insights from Artificial Intelligence and Computational Approaches - Sachdeva, Heena; Sharma, Manish; M, Maninder (Pharmacognosy Reviews)
The global outbreak of Coronavirus Disease 2019 (COVID-19), caused by SARS-CoV-2, has presented significant challenges to healthcare systems. Despite the availability of vaccines and antiviral agents, the evolving nature of viral variants necessitates the exploration of complementary strategies. Immunomodulation, particularly through plant-based agents, has emerged as a promising adjunctive approach to manage COVID-19 by restoring immune balance and attenuating hyperinflammation. This review synthesizes current evidence on immunomodulatory plants and their phytoconstituents, including flavonoids, alkaloids, saponins, and polysaccharides derived from species such as Withania somnifera, Tinospora cordifolia, Curcuma longa, Ocimum sanctum, and Glycyrrhiza glabra. Mechanistic insights into how these phytochemicals modulate immune pathways, including NF-κB, JAK/STAT, and TLR signaling, are discussed. Moreover, we incorporate recent advances involving Artificial Intelligence (AI), molecular docking, and network pharmacology that have accelerated the discovery and optimization of plant-based therapeutics against SARS-CoV-2. The review also examines safety, standardization challenges, and the role of phytomedicines in integrative COVID-19 management protocols, and highlights additional plant species with future potential as immunomodulators.